Ensuring Justice in Access to Investigational Neurological Drugs - Kearns, Lisa; Bateman-House, Alison; Caplan, Arthur (Seminars in Neurology, 2018)
Patients who suffer from life-threatening illnesses or are stricken with conditions that could result in serious morbidity who have exhausted all appropriate treatments may choose to try, through the Food and Drug Administration's expanded access program, an investigational drug or device in development. The program has succeeded for decades in allowing patients to access potentially helpful but still experimental agents. Nevertheless, the administration of investigational drugs outside of clinical trials raises several ethical issues. Of particular concern are the validity of informed consent and the absence of a framework to ensure that experimental drugs are allocated justly and transparently. Although there are some safeguards to help protect the soundness of consent, little work to date has been done to guarantee that investigational medical products are allocated justly and transparently. We introduce a novel pilot project that seeks to address this issue.
Keywords: compassionate use; allocation; investigational drugs; ethics; FDA